A intenção de adoção com base na origem e seu contexto no processo de escolha por café - Sabio, Renata Pozolli (2015)
This study aimed to analyze the context of the attribute of origin in the food choice process and its adoption intention. The research was conducted in three main stages, with the first two being qualitative and the third quantitative. In the first stage, (in-depth interviews) an application of the conceptual model of the food choice process was made, and also it was explored the context of origin for different food categories. Then, a research about how consumers analyze and process the coffee origin was carried out (interviews and focus groups). In this stage there was conducted a comparison between a traditional coffee growing region with a non-traditional region (Minas Gerais and Bahia). Finally, in the last step it was performed an online experiment, in which it was analyzed the intention of adoption for different origins of coffee (Brazil and Colombia). The results showed that when the source is not mentioned, few consumers make a direct association of this attribute as being part of the food choice process. However, it was found that the origin is present and influences the food choices in many ways, even indirectly. With regard to coffee, consumers considered the origin as a source of information about the product and also a differential of quality, mainly flavor. In the comparison between the regions of the Cerrado Mineiro and Bahia, there was a preference for the region that is traditional in growing coffee (Cerrado). The comparison between countries (Brazil and Colombia) showed that the intention of adoption for Brazil's origin of coffee was higher than for coffee originating in Colombia. Still, the relative advantage was the variable that had the highest ratio with the adoption intention, followed by the compatibility. Uncertainty was positively and significantly associated with the intention of adoption for coffee originating in Brazil, but not for the coffee originating in Colombia.